Fostering integration of freshwater ecology with ecotoxicology. (December 2016) - Gessner, Mark O.; Tlili, Ahmed
Summary: Ecology and ecotoxicology have different historical roots, despite their similar names, but are slowly converging to meet the challenge of addressing the massive global proliferation and release of chemicals in the environment. The conceptual, methodological, review and standard research papers in this special issue reflect this emerging trend of blending ecological and ecotoxicological perspectives to assess impacts in freshwater ecosystems. Assessing community and ecosystem impacts of chemical contaminants is complex, however, and will require approaches that explicitly consider biological and chemical diversity as well as the natural variability of environmental factors at multiple spatial and temporal scales. Central themes of the papers in this issue are (i) the importance of indirect effects of chemical contaminants on species interactions and food webs; (ii) effects of multiple stressors, especially interactions between contaminants and environmental factors; (iii) consequences of chemical exposure on ecosystem processes such as primary production and litter decomposition; (iv) the need to account for context dependency and (v) potentially harmful community and ecosystem effects of emerging contaminants, among which nanoparticles are prominently represented. Collectively, these papers show that integrating ecological principles into the design and implementation of ecotoxicological research is essential for assessing and predicting contaminant impacts on biological communities and ecosystems. Conversely, applied ecology and bioassessment would benefit from concepts and approaches developed in ecotoxicology and from fully embracing chemical contaminants as key drivers of community structure and ecosystem processes.